Pemberdayaan masyarakat melalui alih teknologi pembuatan makanan tambahan berbahan baku konsentrat protein ikan di Pulau Cawan Indragiri Hilir - Bintal Amin; Dewita Dewita; Dessy Yoswaty; Irvina Nurrachmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The devotion to the community of Pulau Cawan in Indragiri Hilir Regency carried out in the form of counseling and training which generally aimed at making the community, (especially the cadres of Family Welfare Empowerment or PKK), acquire skills in processing fishbased food and creating new independent businesses. The use and development of Pulau Cawan as an ecotourism area needs to be followed by activities that can improve the welfare of the surrounding community. With the opening of new jobs, it is ultimately expected to improve family welfare. Through this extension and training activities, it is hoped that when fish catch and production abundant or fish prices are falling, it can be saved by processing them into various processed products made from fish, especially snacks and cookies which are of high economic value and nutritious. The results of the activities received good reception and appreciation from the local community, the PKK cadres and Pulau Cawan Headmaster. All the participants confidently will empower their groups to create and start to open businesses in making these fish-based food products. The Head of Department of Maritime Affairs and Fisheries even promised to provide wider assistance for the development of the product, including its marketing.